Impact of waste soot on properties of coal-water suspensions. (1st November 2016) - Staroń, Anita; Banach, Marcin; Kowalski, Zygmunt; Staroń, Paweł
Abstract: The study was conducted in order to implement the principles of Clean Production (CP) in the production of coal-water fuel. Promoting environmentally friendly technologies impact on the reduction of systemic waste, emissions and inputs, which in turn is beneficial to the environment, health and social security. Coal-water suspensions can be a substitute for fuel oil, which from an ecological point of view, is very advantageous with respect to reduced emissions of CO2, SO2 and NOx during the combustion of fuel. To improve the rheological properties of coal-water suspensions, various kinds of additives are used. Coal materials that belong to different assortments: jaret and fine coal and waste soot were used to prepare stable coal-water suspensions. The tests were performed on a laboratory scale in a disc mill. On the basis of the results, the most favourable parameters of process have been chosen (type of raw material and additive content and grinding time). The resulting suspensions are characterised by low viscosity and density, small equivalent diameters and high stability. Gas analysis of burning process of coal-water suspensions with (and without) soot (determination of O2, CO, NO, NO2, SO2, H2 S, H2, CH4 and CO2 ) were conducted and compared. Graphical abstract: Highlights: Coal-water suspensions (CWS) with addition of soot were prepared. Physico-chemical properties of suspensions were determined. Stable coal-water-soot suspensions with preferred utility properties were obtained. The amount of exhausted gases in CWS combustion process was determined. Reduction of emission of hazardous gases during CWS combustion was confirmed.